2011
DOI: 10.1029/2011jc007372
|View full text |Cite
|
Sign up to set email alerts
|

Skin depth at microwave frequencies of sea foam layers with vertical profile of void fraction

Abstract: [1] To develop a foam emissivity model, we started a systematic investigation of sea foam properties at microwave frequencies from 1 to 37 GHz. We first examined various permittivity formulae to find the most suitable one for obtaining the dielectric constant of sea foam. This paper presents an investigation of the skin depth of vertically structured foam layers for the first time. Various void fraction profiles representing variations of foam properties within the foam thickness are examined. The skin depth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 42 publications
5
42
0
1
Order By: Relevance
“…In addition, as reported in [26], the skin depth in the foam layer is larger than that in pure seawater. Considering these, the plots in Fig.…”
Section: Absorption Coefficients Of Foam Layersupporting
confidence: 61%
“…In addition, as reported in [26], the skin depth in the foam layer is larger than that in pure seawater. Considering these, the plots in Fig.…”
Section: Absorption Coefficients Of Foam Layersupporting
confidence: 61%
“…A connection between the thickness of the foam layer and the microwave properties is provided in [11,21]. According to these results, it can be assumed that σ f is equal to a constant, and very low, backscattering value; as it is very well known for very strong winds, when the sea surface is entirely covered by foam, the vertical average backscattering coefficient reduces to a very low value, which obviously coincides with the local backscattering of the foam.…”
Section: Methodsmentioning
confidence: 95%
“…For passive remote sensing of the ocean surface, the foam skin depth dictates our interest in the floating foam layers, excluding deeper bubble plumes [25]. Whitecaps corresponding to the inception of wave breaking are usually thick and bright (visually and radiometrically) and are referred to as active whitecaps.…”
Section: Sea Foam As a Mediummentioning
confidence: 99%
“…It was shown that various functional forms could represent the shape of the void fraction profile in the foam depth [25]. A review of oceanographic data from laboratory and field experiments [25] established a plausible range of foam layer thicknesses encountered in the ocean, from 1 cm to more than 12 cm in active whitecaps and from 0.1 to 1 cm when the whitecaps decay.…”
Section: Sea Foam As a Mediummentioning
confidence: 99%
See 1 more Smart Citation